2014
DOI: 10.1590/s0036-46652014000600011
|View full text |Cite
|
Sign up to set email alerts
|

Hiv and HCV Coinfection: Prevalence, Associated Factors and Genotype Characterization in the Midwest Region of Brazil

Abstract: A cross-sectional study on prevalence, associated factors and genotype distribution of HCV infection was conducted among 848 HIV-infected patients recruited at reference centers in the Midwest Region of Brazil. The prevalence rate of HIV-HCV coinfection was 6.9% (95% CI: 5.2 to 8.6). In multivariable analysis, increasing age, use of illicit drugs (injection and non-injection), a history of blood transfusion before 1994, and the absence of a steady partnership were significant independent associated factors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 50 publications
4
10
0
7
Order By: Relevance
“…Among these 37 studies on the seroprevalence of HCV infection among PLHA [1450], 23 studies were conducted in Brazil, 5 in Argentina, 3 in Cuba, 1 in Puerto Rico, 1 in Chile, 1 in Colombia, 1 in Mexico, 1 in Peru and 1 in Venezuela (Table 1). The sample size varied from 60 to 2,994.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these 37 studies on the seroprevalence of HCV infection among PLHA [1450], 23 studies were conducted in Brazil, 5 in Argentina, 3 in Cuba, 1 in Puerto Rico, 1 in Chile, 1 in Colombia, 1 in Mexico, 1 in Peru and 1 in Venezuela (Table 1). The sample size varied from 60 to 2,994.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the geographic distribution of PLHA coinfected with HCV in Brazil described in these studies. Notably, the southern region had 30 % of all cases [15, 17, 23, 25, 32, 39, 47], followed by the southeast (25.4 %) [19, 24, 4446, 49] and midwest (8.9 %) [14, 35] regions (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…O risco sexual associado à baixa adesão ao uso de preservativo e multiplicidade de parceiros sexuais constituem fatores com elevada prevalência entre soropositivos que apresentam coinfecção. A combinação entre fatores de risco, soropositividade e presença de marcadores sorológicos para o HBV, HCV e T. pallidum, presente também neste estudo, revelam estatisticamente que indivíduos casados, heterossexuais, com idade superior a 35 anos, expostos ao uso de álcool ou drogas ilícitas são os mais vulneráveis a apresentarem alguma coinfecção (5,(14)(15) .…”
Section: Discussionunclassified
“…Recent studies found anti-HCV prevalence in HIV infected individuals of 1.3% in Northeast Brazil, 4.6% in Southeast Brazil, 12.9% in South Brazil, 6.9-9.7% in Midwest Brazil [16,17,[24][25][26]. In all of these studies, HCV genotype 1 was the most prevalent.…”
Section: Hepatitis B and C Prevalence In Patients Infected By Hivmentioning
confidence: 95%